2023
DOI: 10.1080/00325899.2023.2192036
|View full text |Cite
|
Sign up to set email alerts
|

Effect of layer thickness on spatter properties during laser powder bed fusion of Ti–6Al–4V

Abstract: High layer thicknesses for laser powder bed fusion are promising for productivity increase. However, these are associated with increased process instability, spatter generation and powder degradation, crucial for alloys sensitive to oxygen. The effect of increasing layer thickness from 30 to 60 µm is studied focusing on Ti-6Al-4V spatter formation during LPBF and its characterisation, with scanning and transmission electron microscopy, combustion analysis and X-ray photoelectron spectroscopy. Results indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…In the case of stainless steel, chemical composition and crystal structure appear to remain unchanged throughout the transformation from virgin powder to smoulder [20]. For Ti6Al4V, one study detected no change in composition [25] and one study did [26]. However, smoulder particles form a thicker oxide layer than virgin powder counterparts, but this does not affect the bulk properties of particles [27].…”
Section: Introduction and State Of The Artmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of stainless steel, chemical composition and crystal structure appear to remain unchanged throughout the transformation from virgin powder to smoulder [20]. For Ti6Al4V, one study detected no change in composition [25] and one study did [26]. However, smoulder particles form a thicker oxide layer than virgin powder counterparts, but this does not affect the bulk properties of particles [27].…”
Section: Introduction and State Of The Artmentioning
confidence: 99%
“…However, smoulder particles form a thicker oxide layer than virgin powder counterparts, but this does not affect the bulk properties of particles [27]. The thickness of oxide layers on IN718 smoulder particles decreases with lower oxygen content during the build job [25]. Murray et al [28] found an influence of smoulder content on single-track volumes which is rather negligible if it is blended with virgin powder [24].…”
Section: Introduction and State Of The Artmentioning
confidence: 99%